My Dura-Europos the letters of Susan M. Hopkins, 1927-1935 - Hopkins, Susan M.; Goldman, Bernard 1922-2006; Goldman, Norma 1922-2011; Goldman, Bernard 1922-2006 (Detroit [Mich.] Wayne State Univ. Press, 2011)
Introduction: Historical overview and the role of Susan M. Hopkins in the Dura campaigns -- Archaeology, war, and Syria -- Dura-Europos : discovery and recovery -- "Where the journey began" : the summer school at the American Academy in Rome -- The American School of Classical Studies at Athens : excavation experience at Olynthus -- Summer tour in Europe : with the Pillets in Paris -- The road to Beirut via Aleppo -- Maurice Pillet and his American crew -- Beirut to Dura : the journey to the site -- Letters from Dura-Europos : the first joint Yale University and French Academy excavation -- Trip to Baghdad -- Back at Dura : preparations to return to the USA -- Return via Deir ez-Zor, Palmyra, Aleppo, Beirut, Palestine, Jordan -- Traveling back to Greece via Cyprus and Rhodes -- Pillet and after -- The sixth, seventh, and eighth seasons, 1932-35 -- The Dura-Europos synagogue and its paintings -- The return trip of Mary Sue Hopkins Coates to Damascus and to Dura-Europos -- Addendum A: The seasons at Dura-Europos -- Addendum B: The chronology of Dura-Europos -- Addendum C: Those intrepid ladies -- Glossary
Introduction: Historical overview and the role of Susan M. Hopkins in the Dura campaigns -- Archaeology, war, and Syria -- Dura-Europos : discovery and recovery -- "Where the journey began" : the summer school at the American Academy in Rome -- The American School of Classical Studies at Athens : excavation experience at Olynthus -- Summer tour in Europe : with the Pillets in Paris -- The road to Beirut via Aleppo -- Maurice Pillet and his American crew -- Beirut to Dura : the journey to the site -- Letters from Dura-Europos : the first joint Yale University and French Academy excavation -- Trip to Baghdad -- Back at Dura : preparations to return to the USA -- Return via Deir ez-Zor, Palmyra, Aleppo, Beirut, Palestine, Jordan -- Traveling back to Greece via Cyprus and Rhodes -- Pillet and after -- The sixth, seventh, and eighth seasons, 1932-35 -- The Dura-Europos synagogue and its paintings -- The return trip of Mary Sue Hopkins Coates to Damascus and to Dura-Europos -- Addendum A: The seasons at Dura-Europos -- Addendum B: The chronology of Dura-Europos -- Addendum C: Those intrepid ladies -- Glossary.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Hopkins, Susan M -- Correspondence; Hopkins, Clark -- 1895-; Hopkins, Susan M -- Travel; Excavations (archaeology) -- Syria -- Dura-Europos (Extinct city); Synagogues -- Syria -- Dura-Europos (Extinct city); Chapels -- Syria -- Dura-Europos (Extinct city); Archaeologists' spouses -- Correspondence; Dura-Europos (Extinct city); Middle East -- Description and travel; Europe -- Description and travel; Briefsammlung -- 1927-1935